Development of leukocytoclastic vasculitis in a patient with multiple myeloma during treatment with thalidomide - Witzens-Harig, Mathias; Möhler, Thomas; Neben, Kai; Frühauf, Stefan; Hartschuh, Wolfgang; Ho, Anthony Dick; Goldschmidt, Hartmut (Annals of hematology, 2004)
Thalidomide, an agent with antiangiogenic and immunomodulatory properties, is therapeutically effective in multiple myeloma, leprosy, and autoimmune diseases. The most common clinical toxicities of thalidomide are constipation, neuropathy, fatigue, sedation, rash, tremor, and edema. We here describe for the first time a patient who developed leukocytoclastic vasculitis during therapy with thalidomide. Of the 260 patients treated with thalidomide in our institution, this is the first patient who developed autoimmune disease. We conclude that patients with malignant disorders who are treated with thalidomide should be carefully monitored for the development of autoimmune disorders. Whether autoimmune phenomena also occur during treatment with new drugs such as PS-341 or potent immunomodulatory agents remains to be evaluated.
Published online: 19 November 2003
Gesehen am 25.02.2022